MiRNA 106a-5p in cerebrospinal fluid as signature of early relapsing remitting multiple sclerosis: a cross sectional study - Zanghì, Aurora; Manuti, Virginia; Serviddio, Gaetano; D’Amico, Emanuele; Avolio, Carlo (Frontiers in Immunology, 2023)
Background: Circulating microRNAs (MiRNAs) have been investigated for their role in finetuning the adaptive immune response to inflammatory factors and Multiple Sclerosis (MS). They have been investigated as possible biomarkers for the diagnosis and prognosis of the disease.A cross sectional study conducted at MS centre of Foggia, Italy. We enrolled patients with (1) age between 18 and 55 years, (2) a definitive diagnosis of relapsing remitting MS (RRMS) per the revised McDonald criteria, and (4) naïve to any disease modifying therapy or 5) patients with other n eurological disorders (OND). Aim of the study was to compare the levels of expression of miRNA 21-5p, miRNA 106a-5p, miRNA146a-5p, miRNA223-3p in cell-free cerebrospinal fluid (CSF) in RRMS patients and OND. Investigated MiRNAs were extracted, retrotranscripted and then assessed by real-time polymerase chain reaction assay (q-PCR). A receiveroperator characteristic (ROC) curve was used to test MiRNAs as a biomarker for diagnosing MS. A linear regression analysis was done to find any association with disease characteristics at the time of diagnosis.Results: A total cohort of 70 subjects (70% women) was analyzed. Out of them, 35 had a RRMS diagnosis. MiRNA 106a-5p (7.8±3.8 vs 1.3±0.9, p=0.03) had higher levels in RRMS patients when compared to OND. The ROC curve indicated that MiRNA 106a-5p could be considered disease biomarkers with an area under the curve of 0.812 (p<.001; 95% CI 0.686-0.937). Linear regression analysis showed an association between the number of oligoclonal bands and MiRNA 106a-5p levels (B coeff 2.6, p<.001; 95% CI 1.3-4.9). We described miRNA 106a-5p as a possible signature in CSF of RRMS patients in the early phases of the disease. Further studies are needed to characterize their role in early MS as disease biomarkers.